Mono- and dinuclear (η6-arene) ruthenium(II) benzaldehyde thiosemicarbazone complexes: Synthesis, characterization and cytotoxicity - Stringer, Tameryn; Therrien, Bruno; Hendricks, Denver T.; Guzgay, Hajira; Smith, Gregory S.; Stringer, Tameryn; Therrien, Bruno; Hendricks, Denver T.; Guzgay, Hajira; Smith, Gregory S. (My University, 2011)
A series of mono- and dinuclear (η6-arene) ruthenium(II) complexes were prepared by reaction of thiosemicarbazone ligands derived from benzaldehyde and ruthenium(II) precursors of the general formula [Ru(η6-arene)(μ-Cl)Cl]2, where arene = p-iPrC6H4Me or C6H5C3H6COOH. These complexes were characterized by NMR and IR spectroscopy, ESI-mass spectrometry and elemental analysis. The molecular structure of the mononuclear p-cymene complex was determined by X-ray diffraction analysis, revealing a pseudo-tetrahedral piano stool conformation and a bidentate N,S coordination mode of the thiosemicarbazone ligand. The complexes and ligands were evaluated for their in vitro cytotoxicity against the WHCO1 oesophageal cancer cell line.
Keywords: Bioorganometallic chemistry; Arene ruthenium(II); Thiosemicarbazones; Anticancer drugs